Pertumbuhan dan Hasil Beberapa Varietas Jagung Hibrida pada Sistem Tanam Berbeda di Kabupaten Bengkulu Utara - Yartiwi Yartiwi; Yulie Oktavia; Ahmad Damiri; Irma Calista (Seminar Nasional Lahan Suboptimal, 2018)
Yartiwi et al, 2019. Growth and Results of Several Hybrid Corn Varieties in Different Planting Systems in North Bengkulu Regency. pp. 37-42.Corn is one of the agricultural commodities of food crops that have an important role in national development. The purpose of the research was to see the growth viability and the results of several hybrid corn varieties on different planting systems in North Bengkulu Regency. This study was conducted in Yogyabaru Village, Kerkap District, North Bengkulu Regency from April to July 2016. The assessment was carried out using a Randomized Block Design (RBD) with 2 factors. The first factor is the treatment of variety (V) which consists of 3 levels of treatment. The second factor is the spacing (JT) which consists of 2 levels, so that 6 treatment combinations are obtained. Each treatment combination was repeated 5 times. Number of plants sample 10 plants / replications. Analysis carried out on quantitative data observations from vegetative and generative growth component variables using the F test at the level of 5%. If there are significant differences between treatments, further testing is carried out with the LSD test at 5% level. The results of the research showed the length of the cob and the dry seed yield of corn plants of Bisi 18 variety planted with legowo systems is highest compared to Bima 19 Uri and Bima 20 Uri varieties with the tegel planting system.